2006
DOI: 10.1063/1.2345047
|View full text |Cite
|
Sign up to set email alerts
|

Buckling characteristics of SiGe layers on viscous oxide

Abstract: Buckled SiGe films on viscous oxide with different Ge content are studied by wafer bonding and smart-cut process. Compressively strained SiGe layers on the viscous oxide were relaxed to form the buckled state after thermal treatment. Two-dimensional buckling on blanket films is observed. A higher Ge concentration results in a smaller buckling amplitude and a smaller buckling period. Both buckling amplitude and period increase as oxidation time is increased. A small SiGe film ͑mesa͒ area can inhibit buckling. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
4
2
0
Order By: Relevance
“…This partial relaxation is accompanied by the undulation of the layer, the rotation of its crystallographic planes and its swelling and thickening. All the data suggest that this phenomenon can be regarded as the first signs of elastic relaxation at the origin of the buckling mechanism, already reported during high temperature annealing of compressively strained Si 1-x Ge x films on a viscous substrate [39,41,44,45]. This mechanism has been commonly related to the low viscosity of the surrounding oxide, which in our conditions, has a glass transition temperature around 965°C.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…This partial relaxation is accompanied by the undulation of the layer, the rotation of its crystallographic planes and its swelling and thickening. All the data suggest that this phenomenon can be regarded as the first signs of elastic relaxation at the origin of the buckling mechanism, already reported during high temperature annealing of compressively strained Si 1-x Ge x films on a viscous substrate [39,41,44,45]. This mechanism has been commonly related to the low viscosity of the surrounding oxide, which in our conditions, has a glass transition temperature around 965°C.…”
Section: Resultssupporting
confidence: 78%
“…In parallel, it was reported that during high temperature treatment, the SiO 2 film becomes viscous and the strained thin film on this viscous oxide is morphologically unstable. In this case, the relaxation of the film can occur due to the viscous flow of the Si 1-x Ge x film in the underlying oxide layer [39][40][41][42][43][44][45]. In these conditions, the relaxation mechanism to relieve stress results from the buckling of the film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the atomic force microscopy (AFM) and transmission electron microscopy (TEM), they observed that wrinkles patterns were well organized sinusoids and aligned with the < 100 > directions of the cubic crystal Si 0.7 Ge 0.3 with a period of about 1µm and amplitude of about 70-80 nm. Similar experimental observations have been reported by other research groups [22][23][24]. It is believed that it has important potential applications for designing stress relaxation strategies in semiconductor industries [25,26].…”
Section: Introductionsupporting
confidence: 89%
“…Numerical experiments of long time wrinkling evolution processes verified the LSA results, successfully simulated anisotropic wrinkling pattern formation and coarsening, produced a power law scaling and reproduced certain featured phenomena observed in physical experiments. Both the analytical and numerical results are qualitatively in accordance with the physical experiments recently done by several research groups [1,[22][23][24].…”
Section: Introductionsupporting
confidence: 87%